MENTAL IMAGES PROCESSING OF WORDS ABOUT MOBILITY IN PEOPLE WITH VISUAL IMPAIRMENT IN A NON-INCLUSIVE ENVIRONMENT (CARTAGENA, COLOMBIA) - Vázquez-Miraz, Pedro (2022)
In the present exploratory study, the mental representations of concrete and abstract words whose theme revolved around mobility and transport in people with visual disability, all residents of the city of Cartagena de Indias (N=10), were analyzed to those who were presented thirty words (fifteen abstract and fifteen concrete, which were previously evaluated by specialists in cognitive psychology); subsequently, the sample was asked to make a description as detailed as possible of the aforementioned items. The results indicated that half of the participants encountered a high difficulty in representing abstract and concrete words related to daily mobility and transportation.